Looking and Voicing: The Eye, the Gaze and Seeing in Lea Aini’s novel The Rose of Lebanon - Kosh Zohar, Talila (MiKAN, 2016)
Leah Aini’s novel is a literary autobiography written through the stories that the writer/protagonist conveys about a wounded soldier in a hospital with a serious head injury. The novel represents a different Israeli initiation story, written through looking and watching eyes, through the sharp and precise vision of the writer. The narrative tells of a different Israeli reality: the southern fringes of Tel Aviv, border areas, spaces occupied by the ‘others’ - the outsiders who are distanced from the center, neighborhoods of immigrants, refugees, Holocaust survivors and Arabs, crowded shops of small craftsmen and merchants and the ugliness of material and cultural poverty. This reality is reflected through a gaze that in itself is marginal: a feminine gaze that captures what the hegemonic gaze ignores and denies. The gaze is a central thematic element in the novel. It constructs and writes the narrative that in itself is about looking as an act of resistance and survival. The narrator’s gaze ‘voices’ a critical perspective concerning the different Israeli realities. This is the ‘post-colonial’ gaze of a subject born and living in a ‘colony’, a subject who establishes herself under oppression and resists the cultural and social colonization which marks her as inferior: a Mizrahi woman, an unwanted daughter born to a working class family, the descendant of a Holocaust survivor parent. Through the various lenses that paint her gaze in colors of gender, race and ethnicity, the protagonist/writer looks at families, communities and society. Aini deconstructs myths and common beliefs and writes an alternative Israeli ethos, focusing on its silenced and silent aspects. This article examines the voice that articulates the oppositional gaze of the subaltern.